AN ANALYSIS OF ENGLISH TEACHERS’ STRATEGIES IN OPENING THE LESSON IN THE CLASSROOM - ARSETA, NORA; HARAHAP, ALAMSYAH; SYAFRYADIN, SYAFRYADIN (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This research analyzed the strategies used by English teachers in opening learning at SMA N in Bengkulu Selatan. This study aims to find out the most prevalent strategy for opening lessons used by English teachers and why the English teachers choose those strategies in opening learning. The approach used in this research is qualitative with a descriptive research type. The subjects in this study were thirteen English teachers from five SMA N in Bengkulu Selatan. The instruments used in this research were observation checklists, interviews, and documentation. The data were analyzed using data reduction, data presentation, and conclusions. The results showed that the most dominant strategies used by English teachers in opening learning at SMAN N Bengkulu Selatan were focusing attention and arousing students' interest, and generating student motivation. Teachers used those strategies to attract the students' attention and encourage students to be more involved in the learning process. This strategy is believed to be able to create a good relationship between teachers and students.